Petanque Game Modification Training to Enhance the Competence of Adaptive Physical Education Teachers - Febriani Fajar Ekawati; Tri Winarti Rahayu; Ismaryati Ismaryati; Budhi Satyawan; Deddy Whinata Kardiyanto; Bambang Wijanarko; Muhammad Endra Sukmana; Khalil Junan Difa; Abrean Meli Andani (Universitas Lambung Mangkurat, 2026)
The limited variety of adaptive physical activities in Physical Education, Sports, and Health learning at Special Schools (SLB) has constrained teachers’ ability to design instruction that aligns with the characteristics of students with intellectual disabilities. This community service program aimed to enhance teachers’ competence through training on modifying petanque games. The method employed was service learning, an experiential community engagement approach that integrates service provision with hands-on practice. This approach enabled teachers not only to receive theoretical knowledge but also to actively engage in practice and reflection, thereby improving their applied competencies. The program was implemented through pre-implementation, implementation, and evaluation stages involving 10 PJOK teachers at SLB Negeri Surakarta. Evaluation was conducted using pretests and posttests to assess knowledge, while observations were used to evaluate practical skills. The results demonstrated an increase in teachers’ knowledge ranging from 39% to 53%, as well as improved practical abilities in designing PJOK lessons through the modification of game rules, adaptation of equipment, and adjustment of fundamental techniques. The program strengthened teachers’ pedagogical capacity and supported the sustainable development of adaptive physical education learning.